AKP’s Neo-Ottomanism: A Constitutive Component of Neoliberal Hegemony in Turkey? - Gürdal, İlke (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Since 2002, Adalet ve Kalkınma Partisi (AKP) has enjoyed an uninterrupted rule in Turkey. Over the years, it has increased its dominance over society by implementing its agenda and winning every parliamentary election. The party abandoned the traditional conduct of foreign policy in Turkey shaped by Kemalism, setting on course for a new foreign policy orientation. The key research question is: “How does AKP’s foreign policy contribute to the consolidation of neoliberal hegemony in Turkey? This thesis has employed the ‘Hegemony’ concept developed by the Italian philosopher Antonio Gramsci as a useful theoretical lens to understand the foreign policy tools used by the AKP concerning Neo-Ottomanism and the constitution and preservation of its domestic hegemony. This thesis focuses on the relationship between foreign policy and domestic policy and the effects of AKP’s foreign policy on the neoliberal hegemony in Turkey. It has focused on how AKP’s Neo-Ottomanism and the use of Sunni values in the Middle East have provided consent for the neoliberal hegemony. It has also argued that AKP’s Neo-Ottomanist foreign policy has contributed to the capital accumulation process and has provided the bourgeoisie with economic gains, serving the neoliberal hegemony of the bourgeoisie in Turkey.

ÖZ: Adalet ve Kalkınma Partisi (AKP) Türkiye'de 2002 yılından bu yana tek başına iktidardır. Katıldığı her seçimden birinci parti çıkmasının getirdiği avantaj ile yıllardır arzu ettiği tüm politikaları uygulama şansını yakalamış, parlamentodaki gücü sayesinde toplumda egemen bir konuma gelmiştir. Parti, daha önce Türkiyede Kemalist anlayışla şekillenmiş geleneksel dış politika anlayışını terk ederek ‘Yeni Osmanlıcı’ bir dış politika yönelimi gösterdi. Temel araştırma sorum şu: “AKP'nin dış politikası Türkiye'de neoliberal hegemonyanın güçlenmesine nasıl katkıda bulunuyor? Bu tez, İtalyan filozof Antonio Gramsci tarafından geliştirilen 'Hegemonya' kavramını, AKP'nin Neo-Osmanlıcılık ve onun yerel hegemonyasının kuruluşu ve korunması konusunda kullandığı dış politika araçlarını anlamak için yararlı bir teorik mercek olarak kullanmıştır. Bu tez, dış politika ile iç politika arasındaki ilişkiye ve AKP'nin dış politikasının Türkiye'deki neoliberal hegemonya üzerindeki etkilerine odaklanmaktadır. AKP'nin Neo-Osmanlıcılığının ve Ortadoğu'da Sünni değerlerin kullanımının neoliberal hegemonyaya nasıl hizmet ettiğine odaklanılmıştır. AKP'nin Yeni-Osmanlıcı dış politikasının sermaye birikim sürecine katkı sağladığı ve burjuvaziye ekonomik kazanımlar sağladığı, Türkiye'de burjuvazinin neoliberal hegemonyasına hizmet ettiği de bu tezde tartışılmıştır.
Doctor of Philosophy in International Relations. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2022. Supervisor: Assoc. Prof. Dr. Umut Bozkurt.
Keywords: Political Science and International Relations Department; Politics--Political Parties--Adalet ve Kalkınma Partisi (AKP)--Turkey; Elections--Turkey; Turkey--Politics and Government; Foreign policy, AKP, Neoliberalism, Neo-Ottomanism